THE EFFECTIVENESS OF IEPC (IMAGINE, ELABORATE, PREDICT, CONFIRM) STRATEGY TO IMPROVE THE TENTH GRADERS’ READING COMPREHENSION - Heru Setiawan (Global Expert: Jurnal Bahasa dan Sastra, 2016)
The objective of the study was to find out whether teaching reading comprehension through IEPC (Imagine, Elaborate, Predict, Confirm) Strategy had a significant effect on the student’s reading achievement or not. The population of the study was the Tenth Grade Students of State Islamic Senior High School 3 of Palembang in the academic year of 2015/2016. In doing the study, the researcher used quasi-experimental design to two groups of students. The total number of students was 369. The sample was 68 students that were taken by using purposive sampling strategy. Thirty four students were in the experimental group and thirty four students were in the control group. There are two instruments for collecting the data i.e. test and questionnaire. The result showed that teaching reading comprehension through IEPC strategy had a significant effect on the students’ reading achievement. The result of paired sample from experimental group was 10.877. Based on the independent sample t-test analysis, it was found that t-obtained was 11.17 (df=66; p=0.025), the critical value of the test was 1.668, it means there was significant difference between students’ comprehension in reading through IEPC strategy and those who were taught through lecturing.  Keywords : Effectiveness, Improving, Reading Comprehension, IEPC (Imagine, Elaborate, Predict, Confirm) Strategy